LEADERSHIP STYLE AND ITS INFLUENCE ON TEACHER PERFORMANCE IN SMAN 1 GAMBIRAN BANYUWANGI - Nur Ahmadi; Suwignyo Widagdo; Yuniorita Indah (MBA - Journal of Management and Business Aplication, 2018)
The objective of this researchwas to analyze the influence of Leadership Style, Work Atmosphere, and Career Development on Teacher Performance.The object of this research is teacher at SMAN I GambiranBanyuwangi. Type of this research was quantitative causality. Respondents who were samples in this research were 51 teachers consisting of 44 civil servant teachers and 7 non-civil servant teachers. Data analysis tool used in this research was doubled linear regression. Technically, SPSS software version 2.2 was used to analyze the data. Respondents were 51 teachers consisting of civil servant and non-civil servant teachers. The results showed that the leadership style, work atmosphere and teacher career development partially affect the improvement of teacher performance. From the analysis result, three variables simultaneously also affect the performance of teachers. While of the three independent variables studied, the dominant variablewhich affects teacher performance was the principal leadership style. The results of this researchreinforced previous studies which state that leadership style is a very important variable in improving performance. The implications of this research showed that to improve teacherperformance, the principal needed to have a leadership style which is appropriate to the character of the organization he leaded. A supportive working environment would help teachers feel comfortable and secure so that their performance improves. Similarly career development needed to be planned so that teachers had the motivation to improve performance in the long termand it would be the capital to fulfill the expectations in their career development. The advice was given to improve career development performance in SMAN 1 GAMBIRAN is by develop the principal leadership style by the improvement of task oriented stye to support the implementation of the curiculum instead.